Mental training can improve physical activity behavior in adolescent girls - Mahboubeh Ghayour Najafabadi; Amir-Hossein Memari; Ramin Kordi; Monir Shayestehfar; Mohammad-Ali Eshghi (Elsevier, 2017)
Background: Lately, physical activity (PA) in young girls has been frequently discussed, thus we were interested to examine whether a mental training intervention can increase the level of PA in young girls. Methods: A sample of 56 girls aged 15.4 ± 0.3 years (mean ± SD) was assigned to either the intervention or control group. We then conducted a 6-week mental imagery training program on young female participants. PA was evaluated with objective accelerometer monitors. Physical self-concept was also assessed in all participants. Results: Young females' PA increased after a course of mental training compared to female participants in control group. Furthermore, physical self-concept improved related to mental training program. Conclusion: Exercise imagery may be an effective method of PA increase besides psychological enhancement in young girls.